PENGARUH SISTEM PENGENDALIAN INTERN PEMERINTAH TERHADAP EFEKTIVITAS SISTEM INFORMASI MANAJEMEN DAERAH (SIMDA) KEUANGAN (Survey Pada SKPD Pemerintah Kabupaten Sigi) - Josvidar, Noviyanti (Katalogis, 2017)
The purpose of this research is determine and analyze the influence of government internal monitoring system that consists of controlling environment (X1), risk assessment (X2), controlling activities (X3), information and communication (X4), and monitoring (X5) on the effectiveness of local financial management information system (Y). Analysis tool is multiple linear regressions with ordinary least square (OLS) method. Population consists of the total government regionl working units in Sigi Regency and selected 42 units as sample. Respondents are the head of finacial and asset who in charge as financial administrator officials in 42 working units. Research instrument is questionnaire and data is analyzed with multiple linear regressions.Â  The conclusion draws that government internal monitoring system that consists of controlling environment, risk assessment, controlling activities, information and communications, and monitoring simultaneously and partially have positive and significant influence on the effectiveness of local financial management information system. From those variables, controlling environment does not have strong influence on the effectiveness of local financial management information system that resulted unqualified opinion from The National Finance Agency in Central Sulawesi.